A systematic review of genes involved in the inverse resistance relationship between cisplatin and paclitaxel chemotherapy: Role of BRCA1. - STORDAL, BRITTA KRISTINA (Bentham Science, 2009)
A systematic review of cell models of acquired drug resistance not involving genetic manipulation showed that 80% of cell models had an inverse resistance relationship between cisplatin and paclitaxel[1]. Here we systematically review genetically modified cell lines in which the inverse cisplatin/paclitaxel resistance phenotype has resulted. This will form a short list of genes which may play a role in the mechanism of the inverse resistance relationship as well as potential markers for monitoring the development of resistance in the clinical treatment of cancer. The literature search revealed 91 genetically modified cell lines which report toxicity or viability/apoptosis data for cisplatin and paclitaxel relative to their parental cell lines. This resulted in 26 genes being associated with the inverse cisplatin/paclitaxel phenotype. The gene with the highest number of genetically modified cell lines associated with the inverse resistance relationship was BRCA1 and this gene is discussed in detail with reference to chemotherapy response in cell lines and in the clinical treatment of breast, ovarian and lung cancer. Other genes associated with the inverse resistance phenotype included dihydrodiol dehydrogenase (DDH) and P-glycoprotein. Genes which caused cross resistance or cross sensitivity between cisplatin and paclitaxel were also examined, the majority of these genes were apoptosis associated genes which may be useful for predicting cross resistance. We propose that BRCA1 should be the first of a panel of cellular markers to predict the inverse cisplatin/paclitaxel resistance phenotype.
PUBLISHED
Keywords: Cisplatin; Paclitaxel; BRCA1